A Rare Case of Ancient Schwannoma in the Anterior Mediastinum: a Case Report - Khan, Arshi; Ahmed, Murad; Afroz, Nishat; Akhtar, Junaid (Annals of Pathology and Laboratory Medicine, 2025)
Ancient schwannoma is a rare variant of schwannoma that presents histological features mimicking malignancy, often leading to diagnostic challenges. This benign neurogenic tumor originates from Schwann cells of the peripheral nervous system and can develop throughout the sympathetic and parasympathetic nervous systems. Neurofibromas and schwannomas are among the most common benign neurogenic tumors, but their occurrence in the anterior chest wall, particularly in the mediastinum, is exceedingly rare, with limited cases documented in the literature. We report the case of a 45-year-old female who presented with a 6-month history of progressive shortness of breath and chest pain. The final histopathological examination and IHC confirms the lesion to be an ancient schwannoma. These tumors, characterized by distinctive degenerative changes, often present in atypical locations and are associated with diverse clinical manifestations and unpredictable behavior. Thoracoscopic excision is preferred for small to moderate mediastinal schwannomas due to its minimally invasive nature. However, for large tumors, thoracotomy is often required to ensure complete and safe resection. As these tumors are benign, radiotherapy or chemotherapy is usually not needed. Diagnosis relies on histopathology, though imaging aids in preoperative evaluation. No recurrence was observed in this case.